Alternative Income Sources in the Agriculture of Settlements Along the Hortobágy - Bainé Szabó, Bernadett (Acta Agraria Debreceniensis, 2003)
Agriculture has played a dominant role among the income sources of population living along the Hortobágy just like in any other rural areas. I represent the situations of settlements along the Hortobágy by studying four of them, such as Balmazújváros, Hortobágy, Tiszacsege and Egyek. Big companies having worked in the examined settlements had significance in ensuring local working facilities, and restraining people from leaving. Acts dating back to the beginning of the 1990’ies, privatisation, transformation of the state farm and co-operatives have decreased the rate of employment in agriculture. Alternative income sources relating to agriculture, such as bio-farming by alternative plants, herb production and rural tourism will determine the future of agriculture in this area due to the closeness of the Hortobágy National Park, the unique but unfavourable natural conditions for agricultural production, financial aids by the National Agricultural Environmental Programme and the imminent EU-membership. In this way supporting these activities may ensure the livelihood of ex-agricultural workers and alternative income for those working in agriculture.I am going to deal with two issues in this article:• with the change of the role of agriculture in the examined settlements,• with economic analyses of alternative income sources by a model of a family farm.